The Development of Thinking Skill of al-Fiqh Subject by Using Law Box Game for Primary School Students, Year 4 - Cheha, Saifuddin; Sulong, Abdulramae; Hengyama, Muhammdsuhaimi (MENARA : Journal of Islamic and Contemporary Issues, 2022)
The objectives of this research were (1) to develop and determine the effectiveness of the al-Fiqh learning management plan on prayer using the legal box game according to the standard 80 / 80 (2) to develop analytical thinking skills in al-Fiqh courses by using 80 criteria; (3) to compare achievement results. Learning the al-Fiqh course on Salah using the Law Box game between before and after class of students in grade 4 (4) to study the students' satisfaction with the management of the al- Fiqh course by using the law box game. The research tools consist of (1) a game-based learning management plan using legal box games for students in elementary school year 4 in the course of al-Fiqh. (2) Analytical Thinking Skills Assessment Form on prayer (3) learning achievement test to develop analytical thinking skills on prayer (4) student satisfaction assessment form The statistics used were percentage, mean, standard deviation. The results showed that (1) the efficiency value of the learning management plan for developing analytical thinking skills by using the legal box game The overall percentage was equal to E1/E2 = 80.80/83.75 (2) The developing analytical thinking skills was 80.09 percent, which was higher than the specified threshold (80 percent), analyzed by the type t-test. One Sample t-Test satisfies the hypothesis set statistically at the .01 level ( = 80.09, S.D. = 5.63). (3) the comparison of the analytical thinking skills of the al-Fiqh course after studying were higher than before. Statistically significant at .01 ( = 80.80, S.D = 83.75) (4) the assessment of the level of student satisfaction with learning management using the Law Box game overall, the satisfaction level was high ( =4.40, S.D. = 0.72).